PENGARUH STRUKTUR KEPEMILIKAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR CONSUMER CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2020-2023 - Oka, Marcella Tamara; Budiantara, Martinus (ITB AAS Indonesia Surakarta, 2024)
Every year the industrial world experiences very rapid development, resulting in tight competition between organizations or companies. This situation certainly creates various challenges and problems for each company in order to survive. One of the obstacles that is often faced is financial distress. Financial distress refers to a condition where a company's finances begin to decline before bankruptcy occurs. Financial distress can be caused by various aspects, which can come from internal or external sources. One important factor that influences financial distress is the company's ownership structure. In this study, ownership structure is proxied by institutional ownership, management ownership, foreign ownership, and public ownership. The study aims to examine the effect of ownership structure on financial distress. The research population includes all consumer cyclicals sector companies listed on the IDX during 2020-2023, with a sample of 29 companies taken by purposive sampling method. Data analysis uses multiple linear regression analysis which is first tested using the classical assumption test. The results showed that institutional ownership, managerial ownership and public ownership had no significant effect on financial distress, while foreign ownership had a significant negative effect on financial distress.